Influence of wearing blue lenses on Melatonin production and performance in volleyball players - Baptista, E.; Arriel, R. A.; de Castro Carvalho, A. L.; Bispo, M. M. C.; Batista Rodrigues, A.; Souza, H.; Mota, G. R.; Marocolo, M. (Sports Medicine International Open, 2022)
We analyzed the effects of wearing blue lenses on melatonin level, physical and cognitive performance. Fifteen youth volleyball players (15.0±1.5 yrs) attended the laboratory on 3 occasions (48-h interval): on the 1st visit they were familiarized with the procedures of the study, and on 2nd and 3rd visits they were submitted to the testing protocol wearing transparent (control) or blue lens glasses in a counterbalanced crossover design. The protocol consisted of 10 min in "total darkness," 30 min of light stimulation (wearing blue or transparent lenses), followed by an attentional test, and an agility T-test (without wearing the glasses). Samples of saliva (to determine melatonin concentration) were obtained pre- and post-exposure (30 min) to artificial light, wearing the lenses. Sleepiness, alertness, attention, mood, and perceived recovery status and performance variables (reaction time and T-test) were assessed after lens exposure. Melatonin levels did not differ within and between groups (blue lenses, pre: 0.79±0.73 and post: 1.19±1.374 pg/dl, p=0.252, effect size (ES)=0.38; control, pre: 0.97±1.00 and post: 0.67±0.71 pg/dl, p=0.305, ES=-0.35). Nonetheless, melatonin differences were significantly correlated with physical sedation for glasses with blue lenses (r=-0.526; p=0.04). No other variables differed (p>0.05) between protocols, including T-test performance (p=0.07; ES=0.41). Blue lenses do not influence melatonin levels, cognitive/physical performance, and mood status in amateur youth volleyball players.